HUBUNGAN LAMA MENDERITA DIABETES MELITUS DAN KADAR GULA DARAH DENGAN KADAR KREATININ PASIEN DIABETES MELITUS TIPE 2 PADA PEREMPUAN DAN LAKI-LAKI - Rina Kriswiastiny; ketut yoeby sena; Rinto Hadiarto; Toni Prasetia (CV. Jasa Sukses Abadi, 2022)
Diabetes mellitus is a chronic or long-term condition that occurs due to high blood sugar levels caused by the inability of the pancreas to be able to produce enough insulin or even unable to produce insulin. The number of uncomplicated type 2 DM patients who were hospitalized at Pertamina Bintang Amin Husada Hospital Bandar Lampung in the January-October 2021 was 497 patients. This observational analytic study with cross sectional method used a total sampling of 30 samples of type 2 DM patients who met the inclusion criteria. Data collection began in January 2022. Data were evaluated by chi-square test. The research sample was 30 patients with type 2 DM with a duration of suffering >5 years as many as 15 patients and <5 years as many as 15 patients, with a mean blood sugar level (GDS) of 223, the lowest GDS 87 and the highest GDS 530. The mean creatinine level of patients Type 2 diabetes mellitus out of 30 respondents was 0.9 with the lowest creatinine level 0.2 and the highest 3.2. The results of the chi-square correlation between the length of suffering from type 2 diabetes and creatinine levels obtained p value = 0.048, because the p value = 0.048 <0.05 so it can be stated that there is a relationship. In the results of the chi-square correlation between blood sugar levels and creatinine levels, the p value = 0.060, because the p value = 0.060 > 0.05, it can be stated that there is no significant correlation between blood sugar levels and creatinine levels in type 2 DM patients.